Ways to improve accounting, auditing and taxation of business entities in the context of implementing european management practices and introducing artificial intelligence into accounting (Economics and region, 2024)
The article outlines the challenges of improving accounting practices, providing better services to clients, and increasing the profitability of companies. It also analyses how AI-based solutions can speed up calculations, data analysis and reporting, as well as increase efficiency. Furthermore, there was a need for a targeted cloud-based system that generates a wide range of statistics, accounts and indicators with many different potential analytical applications between EU countries and the ability to access them by entrepreneurs from other countries. In a cloud-based predictive accounting platform, artificial intelligence will be able to perform traditionally labour-intensive tasks such as data entry, cost categorisation and invoice reconciliation. As a result, such automation will allow accountants to focus on more strategic activities. In turn, artificial intelligence will analyse patterns in financial data to identify unusual transactions. This is particularly useful in large data sets where manual detection would be impractical. Artificial intelligence and cloud-based systems can significantly reduce staff workload, as well as increase efficiency and accuracy.
Keywords: cloud target system; artificial intelligence; data analysis; EU accounting rules